2020
DOI: 10.1002/maco.202011707
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of copper corrosion in nitric acid

Abstract: The strategy for the permanent disposal of high‐level nuclear waste in Canada involves sealing it in a copper‐coated steel container and burying it in a deep geologic repository. During the early emplacement period, the container could be exposed to warm humid air, which could result in the condensation of nitric acid, produced by the radiolysis of the humid air, on the copper surface. Previous studies have suggested that both nitrate and oxygen reduction will drive copper corrosion, with the nitrate reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Besides, Cu2Cl(OH)3 (17.6°) and Cu2O (37.0°, 43.0°, 61.8°) also appear, which may be formed by corrosion and oxidation of copper foam during the course of electrodeposition. In the acidic Ce(NO3)3 solution, copper can be oxidized to both Cu + and Cu 2+ in the presence of O2 [64], in which Cu 2+ further reacts with local OHnear the surface of copper electrode and Clin the solution to deposit Cu2Cl(OH)3. SEM was utilized to study the morphology change over the course of reaction.…”
Section: In Situ Structural Transformation Of Cu/ce(oh)x Catalystmentioning
confidence: 99%
“…Besides, Cu2Cl(OH)3 (17.6°) and Cu2O (37.0°, 43.0°, 61.8°) also appear, which may be formed by corrosion and oxidation of copper foam during the course of electrodeposition. In the acidic Ce(NO3)3 solution, copper can be oxidized to both Cu + and Cu 2+ in the presence of O2 [64], in which Cu 2+ further reacts with local OHnear the surface of copper electrode and Clin the solution to deposit Cu2Cl(OH)3. SEM was utilized to study the morphology change over the course of reaction.…”
Section: In Situ Structural Transformation Of Cu/ce(oh)x Catalystmentioning
confidence: 99%
“…It has been shown that humid air radiolysis produces HNO 3 [18,21]. The absorption of HNO 3 in condensed water droplets will lead to a decrease in local pH and an increase in the concentration of nitrate that could be an oxidant for copper and other materials [19,22]. To calculate the production rate of HNO 3 in the gas phase by humid air radiolysis, a humid air radiolysis model (HARM) was developed by Morco et al [19].…”
Section: Humid Air and Aqueous-phase Radiolysis Modelsmentioning
confidence: 99%
“…Turnbull et al conducted a series of studies to investigate the effect of nitric acid on copper corrosion as the main oxidant produced under humid air radiolysis [22,60]. By using water droplets containing a range of concentrations of nitric acid exposed to aerated and de-aerated conditions, they demonstrated the slow ability of nitric acid to oxidize copper in the absence of oxygen.…”
Section: Expected Influence Of Irradiation On the Performance Of A Copper-coated Ufcmentioning
confidence: 99%
“…Since copper has wide ranging applications from its use in pipes for plumbing systems, electrical components, heat exchangers, construction materials, industrial machinery, and even cannisters for the storage of nuclear waste, it poses a serious issue that could have major implications. Although copper is protected in neutral and alkaline environments due to the formation of a passive oxide film that covers and protects the surface [1][2][3][4][5][6], it is highly vulnerable to attack in acidic environments where this oxide film readily dissolves thus leaving the metal substrate exposed to corrosive agents [7][8][9][10][11][12][13]. Additionally, aggressive ions such as sulphates, nitrates, and halides can result in degradation of the metal even in neutral and alkaline conditions [14][15][16].…”
Section: Introductionmentioning
confidence: 99%